2021
DOI: 10.1080/15538362.2021.1951922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Crop Loads on Physiological, Yield and Fruit Quality of ‘JoyaTM’ Apple Trees: High Crop Load Decreases Maximum Daily Trunk Diameter and Does Not Affect Stem Water Potential

Abstract: This study aimed to evaluate the effects of different crop load levels on apple trees' yield and physiological characteristics, emphasizing the relationship between stem water potential and crop load and the link between trunk diameter growth and crop load. It was conducted in 2014 at Station Expérimentale Fruits et Légumes (SUDEXPE-CEHM) in Southern France. The 'Joya TM ' apple on Pajam-1 rootstock was used as the plant material. Trees were subjected to hand thinning to obtain four final crop load levels as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
3
1
0
Order By: Relevance
“…With higher radiation and/or VPD, Ψ trunk was lower. However, our results from this study with an SVM model showed that the correlation between VPD and Ψ stem was not linear, which concurs with the results of De Swaef et al [21] and Atay et al [22]. Moreover, both of those studies showed that high VPD values above 2 and 3 kPa did not further reduce stem water potential, which concurs with the results of our SVM model.…”
Section: Discussionsupporting
confidence: 90%
“…With higher radiation and/or VPD, Ψ trunk was lower. However, our results from this study with an SVM model showed that the correlation between VPD and Ψ stem was not linear, which concurs with the results of De Swaef et al [21] and Atay et al [22]. Moreover, both of those studies showed that high VPD values above 2 and 3 kPa did not further reduce stem water potential, which concurs with the results of our SVM model.…”
Section: Discussionsupporting
confidence: 90%
“…The loss of quality (flesh firmness, TSS, DMC, MA content, L/D ratio, and fruit color) with increasing crop load is in line with the findings of Bound [17] and Atay [41] and can be attributed to increased competition for resources with increasing crop load, while the low crop load trees had adequate availability of carbohydrate resources.…”
Section: Fruit Maturity and Qualitysupporting
confidence: 84%
“…This increase in fruit weight can be explained by the early removal of excess floral buds, which prevents wastage of resources, in combination with higher light interception through better fruit positioning contributing to increased carbohydrate production and improved partitioning to targeted fruits [17,30,34]. The reduction in fruit weight with increasing crop load was in line with the previously reported inverse relationship between the fruit number/tree and the final fruit weight [3,4,40,41].…”
Section: Fruit Weight and Yieldsupporting
confidence: 84%
“…These trees would be required to be adequately thinned to improve fruit quality for the current season but also yield a consistent crop load for the following season. Light crop load trees (“OFF”) are associated with bigger fruit sizes that can have storage disorders [ 5 ]. Both phases of the cycle cause a disruption in cropping levels resulting in serious economic losses for the apple industry and can cause significant financial strain on fruit growers.…”
Section: Introductionmentioning
confidence: 99%